Physiological and biochemical effect of neem and other Meliaceae plants secondary metabolites against Lepidopteran insects - Sengottayan, Senthil-Nathan (Frontiers in Physiology, 2013)
This review described the physiological and biochemical effects of various secondary metabolites from Meliaceae against major Lepidopteran insect pest including, Noctuidae and Pyralidae. The biochemical effect of major Meliaceae secondary metabolites were discussed more in this review. Several enzymes based on food materials have critical roles in nutritional indices (food utilization) of the insect pest population. Several research work has been referred and the effect of Meliaceae secondary metabolites on feeding parameters of insects by demonstrating food consumption, approximate digestibility of consumed food, efficiency of converting the ingested food to body substance, efficiency of converting digested food to body substance and consumption index was reviewed in detail. Further how the digestive enzymes including a-Amylases, α and β- glucosidases (EC 3.2.1.1), lipases (EC 3.1.1) Proteases, serine, cysteine, and aspartic proteinases affected by the Meliaceae secondary metabolites was reviewed. Further effect of Meliaceae secondary metabolites on detoxifying enzymes have been found to react against botanical insecticides including general esterases (EST), glutathione S-transferase (GST) and phosphatases was reviewed. Alkaline phosphatase (ALP, E.C.3.1.3.1) and acid phosphatase (ACP, E.C.3.1.3.2) are hydrolytic enzymes, which hydrolyze phosphomonoesters under alkaline or acid conditions, respectively. These enzymes were affected by the secondary metabolites treatment. The detailed mechanism of action was further explained in this review. Acethylcholine esterase (AChE) is a key enzyme that terminates nerve impulses by catalyzing the hydrolysis of neurotransmitter, acetylcholine, in the nervous system of various organisms. How the AChE activity was altered by the Meliaceae secondary metabolites reviewed in detail.